Conflict-induced shocks and household food security in Nigeria - Olanrewaju, Opeyemi; Balana, Bedru (MDPI, 2023)
Conflicts such as the Boko Haram insurgency, herder–farmer conflicts, and armed banditry attacks are major concerns affecting the livelihoods and food security of households in Nigeria. In this paper, firstly, we reviewed and synthesized the nature, spatial extent, and implications of conflicts on food security in Nigeria. Secondly, using survey data and econometric models, we examined the effects of conflict-induced shocks, such as forced migration and fatality on household food security indicators. Our review shows that the underlying causes for the majority of violent conflicts in Nigeria are linked to competition for productive resources, economic inequality, and ethnoreligious tensions. Review results also indicate spatial variations in the nature and severity of violent conflicts in Nigeria. While the Boko Haram insurgency is prominent in the North-East, the North-Central is mainly exposed to herder–farmer conflicts, and there is a high prevalence of communal conflicts in the South-South region of the country. In terms of gender dimensions, women are more vulnerable to conflicts and shoulder more social and economic burdens than men. From our empirical analysis, we found that conflict-induced shocks such as forced migration, fatality, abduction, and injury significantly exacerbate the severity of food insecurity and deteriorate the dietary diversity of households. Conflicts also affect agricultural investment decisions with a negative consequence on future agricultural productivity and food security. Based on the findings, the key policy suggestions include the need for tailored interventions to resolve state or region-specific conflicts, policy interventions on property/land rights and livestock management systems to address herder–farmer conflicts, and targeted investments in building the resilience capacity of households.